DNA barcoding of sawih (Duabanga moluccana) using ISSR marker - Diyanah Musfirah, Bt. Jamal (Universiti Malaysia Sarawak (UNIMAS), 2011)
Duabanga moluccana or locally known as Sawih is a widely known forest tree species for its multi-purpose timber and other natural products such as fibers. Genetic diversity investigation of this species can provide baseline information for indirect selection in tree improvement programme. This study has employed Inter Simple Sequence Repeat (ISSR) technique to assess the genetic diversity and relatedness within and between three populations of D. moluccana located in Sarawak, namely, Mukah, Tatau (Bintulu) and Niah. A total of 73 loci from 90 individuals were successfully amplified with three selected ISSR primers and the percentage of polymorphic loci was 100%. The Shannon’s diversity index showed that D. moluccana in Mukah natural forest (0.4993) was the most diverse compared to Tatau (Bintulu) (0.3795) and Niah natural forest (0.3304). Dendrograms were constructed using unweighted pair group method with arithmetic mean (UPGMA) to show relationship within and among the selected populations. The overall populations were mainly clustered into three main groups, according to their corresponding population. Based on these results, it implies that D. moluccana trees are genetically diverse and related both within and among populations.